Electrophoretic Deposition of Carbon Nanotubes over TiO2 Nanotubes: Evaluation of Surface Properties and Biocompatibility - Jung Eun Park; Il Song Park; Tae Sung Bae; Min Ho Lee (Bioinorganic Chemistry and Applications)
Titanium (Ti) is often used as an orthopedic and dental implant material due to its better mechanical properties, corrosion resistance, and excellent biocompatibility. Formation of TiO2 nanotubes (TiO2 NTs) on titanium is an interesting surface modification to achieve controlled drug delivery and to promote cell growth. Carbon nanotubes (CNTs) possess excellent chemical durability and mechanical strength. The use of CNTs in biomedical applications such as scaffolds has received considerable attention in recent years. The present study aims to modify the surface of titanium by anodizing to form TiO2 NTs and subsequently deposit CNTs over it by electrophoretic deposition (EPD). Characteristic, biocompatibility, and apatite forming ability of the surface modified samples were evaluated. The results of the study reveal that CNTs coating on TiO2 nanotubes help improve the biological activity and this type of surface modification is highly suitable for biomedical applications.